Model formulation in analysis linkage of institutional supply chain to performance and competitiveness (case study in SMEs' clusters of tofu stick in Tinalan village, Kediri city, East Java, Indonesia). (2nd August 2019) - Mustaniroh, Siti Asmaul; Septifani, Riska; Silalahi, Rizky Luthfian Ramadhan; Andavidar, Shufi Mujahida
The problems of SMEs' tofu stick are difficulty to fulfil raw materials requirement if demand was increasing rapidly, and performance has not been maximal yet, followed by high competitiveness. Models in supply chain had not been structured in relation to performance and competitiveness, so systematic model development was necessary to be implemented. This study aimed to improve a model for analysis linkage performance, institution of supply chain and competitiveness of SMEs. The method of analysis used was partial least squared with institutional supply chain, the SMEs performance and competitiveness. The model indicated that the institutional supply chain had a positive and significant impact on the performance and the competitiveness of SMEs, as supported by trust and skilled manpower. However, the SMEs' performance did not significantly affect the competitiveness. Managerial implication in this research is SMEs' need to enforce synergism of institutional supply chain and performance to maximise the goals of business.